Tin cup [videorecording (DVD)] - Shelton, Ron, 1945-; Costner, Kevin; Russo, Rene; Marin, Cheech; Johnson, Don, 1950- (Warner Home Video, 1997)
Psychiatrist Molly Griswold is big city; driving-range pro Roy McAvoy is small time, and he believes only the grandest of gestures can lure her away from a slick touring golf pro and earn her love. So Roy and his dutiful caddy set out to do the impossible: win the U.S. Open.